Parasitoid of the Citrus Leafminer, Cirrospilus ingenuus Gahan (Insecta: Hymenoptera: Eulophidae) - Marjorie A. Hoy; Ru Nguyen (EDIS)
This document provides an overview of the parasitoid Cirrospilus ingenuus Gahan, detailing its introduction, establishment, and biological control role against the citrus leafminer in Florida. It describes the parasitoid's identification, life cycle, host specificity, and ecological impact. The document also discusses the challenges and successes of the classical biological control program, highlighting the interactions between Cirrospilus ingenuus and other natural enemies of the citrus leafminer. Published: October 2003.